Apelin‐13 administration protects against ischaemia/reperfusion‐mediated apoptosis through the FoxO1 pathway in high‐fat diet‐induced obesity. (20th April 2016) - Boal, Frederic; Timotin, Andrei; Roumegoux, Jessica; Alfarano, Chiara; Calise, Denis; Anesia, Rodica; Parini, Angelo; Valet, Philippe; Tronchere, Helene; Kunduzova, Oksana
Abstract : Background and Purpose: Apelin‐13, an endogenous ligand for the apelin (APJ) receptor, behaves as a potent modulator of metabolic and cardiovascular disorders. Here, we examined the effects of apelin‐13 on myocardial injury in a mouse model combining ischaemia/reperfusion (I/R) and obesity and explored their underlying mechanisms. Experimental Approach: Adult male C57BL/6J mice were fed a normal diet (ND) or high‐fat diet (HFD) for 6 months and then subjected to cardiac I/R. The effects of apelin‐13 post‐treatment on myocardial injury were evaluated in HFD‐fed mice after 24 h I/R. Changes in protein abundance, phosphorylation, subcellular localization and mRNA expression were determined in cardiomyoblast cell line H9C2, primary cardiomyocytes and cardiac tissue from ND‐ and HFD‐fed mice. Apoptosis was evaluated by TUNEL staining and caspase‐3 activity. Mitochondrial ultrastructure was analysed by electron microscopy. Key Results: In HFD‐fed mice subjected to cardiac I/R, i.v. administration of apelin‐13 significantly reduced infarct size, myocardial apoptosis and mitochondrial damage compared with vehicle‐treated animals. In H9C2 cells and primary cardiomyocytes, apelin‐13 induced FoxO1 phosphorylation and nuclear exclusion. FoxO1 silencing by siRNA abolished the protective effects of apelin‐13 against hypoxia‐induced apoptosis and mitochondrial ROS generation. Finally, apelin deficiency in mice fed a HFD resulted in reduced myocardial FoxO1 expression and impaired FoxO1 distribution. Conclusions and Implications: These data reveal apelin as a novel regulator of FoxO1 in cardiac cells and provide evidence for the potential of apelin‐13 in prevention of apoptosis and mitochondrial damage in conditions combining I/R injury and obesity.